THE BIBLE'S VIEWPOINT OF LONG-TERM ASSETS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article examines the essence of the statistical and dynamic approach of asset accounting in public administration. The essence of the basic principles of long-term asset accounting has been studied.